2020
DOI: 10.3389/fpsyg.2020.02134
|View full text |Cite
|
Sign up to set email alerts
|

How Our Gaze Reacts to Another Person’s Tears? Experimental Insights Into Eye Tracking Technology

Abstract: Crying is an ubiquitous human behavior through which an emotion is expressed on the face together with visible tears and constitutes a slippery riddle for researchers. To provide an answer to the question “How our gaze reacts to another person’s tears?,” we made use of eye tracking technology to study a series of visual stimuli. By presenting an illustrative example through an experimental setting specifically designed to study the “tearing effect,” the present work aims to offer methodological insight on how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…anger; surprise; happiness; fear; disgust; sadness) if they thought the animal was expressing such, or to indicate that the animal’s expression was emotionally “neutral” if they felt that was the case. We then applied a dichotomous classification based on previous works: emotion, if any, versus emotionless [ 11 , 16 ]. “Emotionless” indicated faces with no perceived expression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…anger; surprise; happiness; fear; disgust; sadness) if they thought the animal was expressing such, or to indicate that the animal’s expression was emotionally “neutral” if they felt that was the case. We then applied a dichotomous classification based on previous works: emotion, if any, versus emotionless [ 11 , 16 ]. “Emotionless” indicated faces with no perceived expression.…”
Section: Methodsmentioning
confidence: 99%
“…There is much scientific evidence to show that humans are extraordinarily apt at detecting micro-nuances that alter their emotional perception when judging another human’s face, and our reaction to emotional tears is the perfect example [ 9 ]. Tears running down a cheek are capable of changing our bioelectric brain activity [ 10 ], and even alter the typical visual inspection pattern in such a way that tears act as magnets of attention [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that tearful individuals are perceived as more honest (Brooks, 2011;, sincere (Gračanin et al, 2021;Picó, Espert, et al, 2020), and reliable (Picó, Gračanin, et al, 2020). Picó, Espert, et al (2020) and Picó, Gračanin, et al (2020) exposed participants to photographs of tearful (vs. non-tearful) people paired with information on specific transgressions and found that the tearful individuals were rated as kinder, more reliable, and more remorseful. Similarly, Hornsey et al (2020) found that when public apologies were accompanied by tears (vs. no tears), they were perceived as more sincere, and the transgressors were considered more remorseful.…”
Section: Communionmentioning
confidence: 99%
“…Morality. There is evidence that tearful individuals are perceived as more honest (Brooks, 2011; Zickfeld et al., 2021), sincere (Gračanin et al., 2021; Picó, Espert, et al., 2020), and reliable (Picó, Gračanin, et al., 2020). Picó, Espert, et al.…”
Section: The Social Function Of Emotional Tearsmentioning
confidence: 99%
“…In humans, emotions are automatically transmitted through visual cues, including non-verbal behaviours such as facial expressions and body language (Picó, 2020). While gazing is unique amongst non-verbal behaviours in that the eye is a sensory organ often associated with the gathering of information, at the same time, it performs the function of sending signals to others.…”
Section: Empathy and Eye-gazementioning
confidence: 99%